Frasques de Mars 96. - Université de Bourgogne, Dijon; Bacon, Francis; Bailly, Jean-Luc; Bonnassieux, Bernard; Cevoz-Goyat, André; Curtil-Faivre, Michèle (Dijon : Institut Universitaire de Technologie, 1996)
Bernhardt, B. ; Colin, S. ; Combard, F. ; Destrés, P. ; Dubief, T. ; D.Field ; M., Gaspard R. et Michèle ; Gérard, N. ; Hannecart, M. ; Khiri, A. ; Munden, G. ; Parisot, M. ; Richard, G. ; Rivière, R. ; Stoulig, F. ; Villerey, T. ; Vincent, T.
Frans
boek